Ultrasound Versus Fluoroscopy for Stellate Ganglion Block: A Cadaveric Study. Issue 10 (29th May 2021) - Hughey, Scott; Schafer, Jeffrey; Cole, Jacob; Booth, Gregory; Tuttle, Ralph; Stedje-Larsen, Eric
Abstract: Objective: Post-Traumatic Stress Disorder (PTSD) is a common psychiatric disorder. Recent investigations have demonstrated effectiveness of Stellate Ganglion Blocks (SGB) for reducing symptoms associated with PTSD. Both fluoroscopic guided and ultrasound guided SGB have been described and are regularly used in clinical practice. This study sought to evaluate differences in block performance when comparing fluoroscopic versus ultrasound guided SGB. Design: Cadaveric Pilot Study. Setting: Academic Research Laboratory. Subjects: Ten Soft-Cured Human Cadavers. Methods: Ten soft-cured human cadavers were used after being at room temperature for 3 hours. Fluoroscopic and ultrasound guided injections were both performed on each cadaver, randomized to left or right sidedness. In total, 7 mL of omnipaque and methylene blue (5:1) was injected in each side. Injectate spread was assessed by measuring vertebral body spread under fluoroscopy. Successful staining of the sympathetic trunk was assessed under cadaveric dissection, with visualization of the sympathetic trunk stained with methylene blue. Results: Ultrasound guided injections resulted in successful staining in 9 of 10 injections, while 6 of 10 for fluoroscopic guidance ( P  = .3034). The average spread in the ultrasound group was 4.0 compared with 5.2 for the fluoroscopic group ( P =.088). In the four fluoroscopic guided injections which failed to stain, the injection occurred posterior to the prevertebral fascia. In the single ultrasound guided block that failed to stain, the injection was in the carotid sheath. Conclusions: While there appeared to be a trend favoring ultrasound guidance, no statistical significance was achieved. This was likely due to this being a limited pilot study. Numerous limitations exist in cadaveric studies, and future investigations should be completed to further study this comparison. That said, the use of the SGB may provide significant relief for patients suffering with PTSD.